System Usability Scale (SUS)–Based Evaluation of the PQX Study Program Archival System - Rahmi Elviana; Delfebriyadi; Fina elfianti (Universitas Putra Indonesia YPTK Padang, 2026)
Digital transformation has encouraged higher education institutions to implement archival information systems in order to improve the efficiency and effectiveness of records management. The PQX Study Program plans to utilize a digital archival information system as the primary medium for archival services; however, technical constraints and indications of low system usability have been identified. This study aims to analyze the usability of the archival information system in the PQX Study Program using the System Usability Scale (SUS) method. The research adopts a software engineering approach employing the Waterfall System Development Life Cycle (SDLC) model, which consists of requirements analysis, system design, prototype implementation, and evaluation stages. System testing was conducted through black box testing to verify system functionality, while usability evaluation was carried out using the SUS based on user perceptions. The results of the black box testing indicate that the application’s functional aspects are valid and operate as expected. Meanwhile, the SUS evaluation involving 10 respondents produced an average score of 60.25, which is below the SUS benchmark score of 98 and falls into category D. These findings suggest that the levels of effectiveness, efficiency, and user satisfaction remain suboptimal, indicating the need for improvements in interface design, process flow, and system usability support.